(untitled) (Nativa, 2025)
This study examines the genetic diversity of Pinus thunbergii populations across various biogeographic regions in Japan, with a focus on the influence of geographic and environmental factors on genetic variation. Using seven EST-SSR markers, the objective was to analyze the influence of geographic factors, gene flow, and historical events on population structure. The research also compared the utility of EST-SSR markers with six genomic SSR (G-SSR) markers, revealing significant differences between them. EST-SSR markers showed lower genetic diversity compared to G-SSR, which could indicate higher inbreeding or reduced gene flow due to their location within genes. Differences in allele numbers, observed and expected heterozygosity, and inbreeding coefficients indicated substantial genetic variations among the studied P. thunbergii populations. Additionally, the comparison between marker types reinforces the importance of methodological choice in genetic diversity assessments. This research provides valuable insights into the genetic diversity patterns of P. thunbergii populations, highlighting the crucial role of markers and geographic regions in understanding the dynamics of genetic variation, with important implications for biogeography and species conservation. Keywords: biogeography; EST-SSR marker; genetic diversity. Padrões biogeográficos da diversidade genética: um estudo de caso das populações de Pinus thunbergii no Japão RESUMO: Este estudo investiga a diversidade genética das populações de Pinus thunbergii em diferentes regiões biogeográficas do Japão, focando no impacto dos fatores geográficos e ambientais sobre a variação genética. Utilizando sete marcadores EST-SSR, o objetivo foi analisar a influência de fatores geográficos, fluxo gênico e eventos históricos na estrutura genética das populações. A pesquisa também comparou a utilidade dos marcadores EST-SSR com seis marcadores genômicos SSR (G-SSR), revelando diferenças significativas entre eles. Os marcadores EST-SSR apresentaram menor diversidade genética em relação aos G-SSR, o que pode indicar maior endogamia ou menor fluxo gênico devido à sua localização dentro de genes. Diferenças no número de alelos, heterozigosidade observada e esperada, bem como no coeficiente de endogamia, indicaram variações genéticas substanciais entre as populações de P. thunbergii estudadas. Além disso, a comparação entre os tipos de marcadores reforça a importância da escolha metodológica nas avaliações de diversidade genética. Esta pesquisa oferece insights valiosos sobre os padrões de diversidade genética das populações de P. thunbergii, destacando o papel crucial dos marcadores e das regiões geográficas para entender as dinâmicas de variação genética, com implicações importantes para a biogeografia e a conservação da espécie. Palavras-chave: biogeografia; marcador EST-SSR; diversidade genética.